The Representation of Women in Pendhoza's Bojoku Galak's Song through Sara Mills's Critical Discourse Analysis Model - Hariyana, Agustinus; Rasyid, Yumna; ., M.Pd; Anwar, Miftahulkhairah; M.Phil, M.Hum (KnE Social Sciences, 2020)
This study considers the representation of women in the lyrics of a popular dangdut song called Bojoku Galak. The study focuses on songs as a poetic form, and this song was selected owning to its popularity in Indonesia. The study uses a qualitative approach with the Sara Mills critical discourse analysis (CDA) model. Research data in the form of vocabulary, phrases, or sentences showing the image of women were taken from in the lyrics. The results showed that the representation of women can be seen from the position of subject-object, and writer-reader. The song represents male actors as subjects and women as objects to be blamed and depicted as ferocious, accusatory, selfish, and uncaring. This contradictions the established representation of women in Indonesian society, which represents women using images of patience, obedience, meek and soft. Keywords: CDA Sara Mills Model, image of woman, descriptive qualitative methods